2002
DOI: 10.1097/00003246-200204001-00002
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in the presentation and outcome of out-of-hospital cardiopulmonary arrest: A multiyear, prospective, population-based study

Abstract: In cases of out-of-hospital sudden cardiac arrest, women have significantly better resuscitation rates than men, especially when controlling for age, particularly among women with non-ventricular fibrillation/ventricular tachycardia presentations. Additional studies are required to validate these observations, not only for long-term survival and external validity, but also for other potential genetic factors and potential discrepancies with other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 34 publications
2
80
0
4
Order By: Relevance
“…Women are less likely to have witnessed arrests, bystander CPR, EMS CPR, and intravenous (IV) medications. 11,27 There is also controversy with respect to survival advantage for women for shockable or other rhythms. 28,29 Six studies to date have evaluated the age-sex interaction.…”
Section: Academic Emergency Medicinementioning
confidence: 99%
“…Women are less likely to have witnessed arrests, bystander CPR, EMS CPR, and intravenous (IV) medications. 11,27 There is also controversy with respect to survival advantage for women for shockable or other rhythms. 28,29 Six studies to date have evaluated the age-sex interaction.…”
Section: Academic Emergency Medicinementioning
confidence: 99%
“…Women are less prone to ventricular arrhythmias except long QT-induced torsade de pointes and drug-induced ventricular arrhythmia, and the incidence of sudden cardiac death is generally lower in women than in men. 46,47 An analysis of the Framingham population revealed that women had a significantly lower incidence of sudden cardiac death in all age groups, with almost two-thirds occurring in subjects without previous diagnoses of coronary artery disease. 47 The lower rate of coronary artery disease in women may contribute to the lower incidence of sudden cardiac death; 48,49 however, differences in susceptibility to ventricular arrhythmia may also play a role.…”
Section: Implantable Cardioverter Defibrillatormentioning
confidence: 99%
“…Reproduced with permission from Albert et al 21 A prospective population-based study in Dallas of outof-hospital cardiac arrest found that women more often presented with asystole and pulseless electrical activity, and men usually had ventricular tachycardia and ventricular fibrillation. 20 In a retrospective analysis of 355 survivors (271 men, 84 women) of out-of-hospital cardiac arrest survivors in Boston, the only independent predictor of cardiac mortality and total mortality in women was the presence of coronary artery disease. A left ventricular ejection fraction (LVEF) <40%, which was the strongest independent predictor of total and cardiac mortality in men, did not have the same prognostic significance in women.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 99%